The Effect of Capital Intensity, Green Accounting, Capital Structure, And Leverage on Tax Avoidance - Regita Bunga Safitri; Indah Rahayu Lestari (Universitas Budi Luhur, 2026)
This study aims to determine the effect of capital intensity, green accounting, capital structure, and leverage on tax avoidance. The population of this study consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) in their financial reports and sustainability reports for the period 2020–2024. The sampling technique used in this study is purposive sampling with a final sample of 175 data from 35 companies. The data analysis technique used was multiple linear regression analysis with the assistance of the Statistical Package for the Social Sciences (SPSS) software version 22. The results of the study indicate that capital intensity has a negative and significant effect.